Pencegahan Penyakit Kanker Payudara dengan Bioinformatika : Membangun Masa Depan Kesehatan - Rifani Khairani Pohan; Juan Dini; Mutiarani Mutiarani; M. Iqbal; Fatur Rahman (Jurnal Sistem Informasi dan Ilmu Komputer, 2025)
Bioinformatics can help identify cancer risk factors, predict cancer, and develop effective prevention strategies. The development of bioinformatics technologies such as genetic data analysis, development of prediction models, and personalization of treatment have opened up new opportunities in cancer prevention. This research aims to examine the role of bioinformatics in preventing cancer and building a better health future. By understanding the potential of bioinformatics, we can develop effective prevention strategies and improve people's quality of life. Prevention and efforts to control breast cancer were discovered using bioinformatics technology. This research shows that the implementation of bioinformatics has a positive impact on efforts to prevent breast cancer for the future of health.